Control of the noise production in a supersonic jet impinging an inclined plate using grooved surface. (October 2022) - Qi, Longzhou; Feng, Heying; Zhang, Rongping; Okolo, Patrick N.; Zhao, Kun
Abstract: This paper presents an experimental investigation on free jet and jets impinging on smooth and grooved surfaces. Acoustic studies are performed using free-field microphones, while two dimensional (2D)-particle imaging velocimetry (PIV) is utilized to investigate the velocity fields. The effects of nozzle-plate spacing distance, nozzle pressure ratio ( NPR ) and plate inclination are also investigated. The results demonstrate that a high-speed jet impinging on a grooved plate generates lesser acoustic radiation on an inclined plate surface when compared to a smooth plate with 2.16 <  NPR  < 3.1 in the range of L/d  = 3 ∼ 5. Reduction of the amplitude of discrete tones is an important factor in its noise reduction. To present a detailed explanation of this phenomenon, this paper further coupled the acoustic discrete tones and mean fluctuating flow velocities. Results showed that screech tone is mainly caused by the interaction between the rear edge of the fourth shock cells and the large vortical structures in the mixing layer, and the shear layer of the wall-jet has a certain shielding effect on the near-wall acoustic power, and the acoustic power decreases at high-speed impinging jets.